A Straightforward Methodology for QCA Circuits Design - Domingues, Julio Saraçol; da Rosa, Leomar Soares; Marques, Felipe de Souza (Symposium on Integrated Circuits and Systems Design (SBCCI); 2020: Anais do XXXIII Symposium on Integrated Circuits and Systems Design, 2020)
The complementary metal-oxide-semiconductor (CMOS) has been used as the main technology to design integrated circuits in the last decades. However, this technology is near to its physical limits. This way, several new devices have been proposed for the replacement of the transistors, such as the Field-Coupled Nanocomputing (FCN). Many FCN paradigms are being studied, including quantum-dot cellular automata (QCA) and nanomagnetic logic (NML). This work proposes a new methodology for QCA synthesis, which attaches different logic and physical synthesis tools, filling gaps, and proposing new methods and elements for integration. Experiments show that our methodology enables the synthesis tools to find smaller QCA circuits compared to previous works.